Impact of the Suspension of Checkpoints on Road Accident Severity: ผลของการยกเลิกจุดตรวจชั่วคราวต่อความรุนแรงของอุบัติเหตุทางถนน - Tunsuparp, Supapong (Journal of Applied Economics and Management Strategy, 2022)
บทคัดย่อ การเสียชีวิตจากอุบัติเหตุทางถนนเป็นหนึ่งในสาเหตุสำคัญของการเสียชีวิตของคนไทยในแต่ละปี โดยสาเหตุที่สำคัญของการเกิดอุบัติเหตุบนท้องถนนได้แก่ การเมาแล้วขับ ซึ่งเป็นอันตรายแก่ตนเอง และผู้อื่นบนท้องถนน เครื่องมือที่สำคัญอย่างหนึ่งในการลดปัญหาการเมาแล้วขับคือการตั้งด่านตรวจแอลกอฮอล์ อย่างไรก็ตามในช่วงเดือนตุลาคมปี 2563 สำนักงานตำรวจแห่งชาติได้มีคำสั่งยกเลิกด่านตรวจ การยกเลิกด่านตรวจอาจทำให้คนมีพฤติกรรมเสี่ยงที่มากขึ้น เนื่องจากโอกาสจะโดนจับเมื่อมีพฤติกรรมเสี่ยงนั้นลดลง การวิจัยครั้งนี้ต้องการที่จะศึกษาผลของการยกเลิกด่านตรวจต่อจำนวนผู้บาดเจ็บหรือเสียชีวิตในอุบัติเหตุแต่ละครั้ง โดยใช้ข้อมูลของศูนย์เทคโนโลยีสารสนเทศและการสื่อสาร สำนักงานปลัดกระทรวงคมนาคม และฐานข้อมูลมูลนิธิศูนย์ข้อมูลจราจรอัจฉริยะไทย ในการวิเคราะห์การถดถอยพหุคูณเชิงเส้น ผลจากการศึกษาพบว่า การยกเลิกการตั้งจุดตรวจนั้นมีผลต่อจำนวนผู้บาดเจ็บหรือเสียชีวิตจากอุบัติเหตุอย่างมีนัยสำคัญทางสถิติ นอกจากนั้นยังพบปัจจัยอื่น ๆ ที่ส่งผลต่อจำนวนผู้บาดเจ็บหรือเสียชีวิตอย่างมีนัยสำคัญ โดยความหนาแน่นของการจราจร และถนนทางโค้งมีผลในทางลบต่อจำนวนผู้บาดเจ็บหรือเสียชีวิต ขณะที่เมื่อเทียบกับรถประเภทอื่นๆแล้ว การใช้รถจักรยานยนต์ มีผลต่อการบาดเจ็บหรือเสียชีวิตเมื่อเกิดอุบัติเหตุมากขึ้น จากผลดังกล่าวให้ข้อเสนอแนะที่สำคัญต่อการพัฒนาการตั้งจุดตรวจ และการรณรงค์เพื่อลดพฤติกรรมเสี่ยงโดยเจาะจงกลุ่มเสี่ยงได้ ABSTRACT Road traffic accidents are one of the leading causes of death in Thailand each year. The main cause of the accidents is drunk driving, which is harmful to the drunk drivers and other drivers nearby. One of the important measures to reduce crash numbers is police checkpoints. However, in October 2020, there was an order by Royal Thai Police to suspend the checkpoints. This suspension might increase risky driving behaviors since there is a lesser chance of being arrested by police. This research, therefore, aims to study the impact of the suspension of checkpoints on the number of injuries or deaths in each accident. Data used in this study is from Office of Information Technology and Communication, Office of the Permanent Secretary, Ministry of Transport, and Intelligent Traffic Information Center. The results from multiple linear regression models show that the suspension of police checkpoints has a positive relationship with the number of injuries or deaths in each accident, and the relationship is statistical significance. In addition, other factors present statistically significance to the number of injuries or deaths in each accident. Traffic density and curved road have a negative relationship with the number of injuries or deaths in each accident while riding a motorcycle has a positive relationship. The results provide suggestions to improve checkpoints and to promote risk-free behaviors to vulnerable groups.